2016
DOI: 10.1126/sciimmunol.aah6109
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of T and B cell repertoire diversity in patients with RAG deficiency

Abstract: Recombination Activating Genes 1 and 2 (RAG1 and RAG2) play a critical role in T and B cell development by initiating the recombination process that controls expression of T cell receptor (TCR) and immunoglobulin genes. Mutations in the RAG1 and RAG2 genes in humans cause a broad spectrum of phenotypes, including severe combined immune deficiency (SCID) with lack of T and B cells, Omenn syndrome, leaky SCID, and combined immune deficiency with granulomas or autoimmunity (CID-G/AI). Using next generation sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
75
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 49 publications
12
75
0
1
Order By: Relevance
“…B‐cell self‐reactivity has been associated with variations in the hydrophobicity profile of the IGH‐CDR3 region that normally contains a discrete proportion (~15%) of tyrosine residues. We have observed a significant reduction in the frequency of tyrosine in the IGH‐CDR3 region of peripheral B cells from patients with RAG defects, irrespective of their clinical phenotype, and we have documented that this abnormality is caused by decreased usage of the IGHJ6 gene segment, confirming recent observations from the van der Burg laboratory . Moreover, an increased proportion of class‐switched immunoglobulin heavy chain transcripts (especially of IGHE transcripts) and a higher rate of somatic hypermutation were observed in the periphery of OS patients .…”
Section: Genotype‐phenotype Correlation In Rag Deficiencysupporting
confidence: 88%
See 1 more Smart Citation
“…B‐cell self‐reactivity has been associated with variations in the hydrophobicity profile of the IGH‐CDR3 region that normally contains a discrete proportion (~15%) of tyrosine residues. We have observed a significant reduction in the frequency of tyrosine in the IGH‐CDR3 region of peripheral B cells from patients with RAG defects, irrespective of their clinical phenotype, and we have documented that this abnormality is caused by decreased usage of the IGHJ6 gene segment, confirming recent observations from the van der Burg laboratory . Moreover, an increased proportion of class‐switched immunoglobulin heavy chain transcripts (especially of IGHE transcripts) and a higher rate of somatic hypermutation were observed in the periphery of OS patients .…”
Section: Genotype‐phenotype Correlation In Rag Deficiencysupporting
confidence: 88%
“…More recently, high‐throughput sequencing techniques have permitted a more detailed and extensive characterization of T‐ and B‐cell repertoire. In particular, we have observed progressive reduction in diversity and increased clonality when moving from patients with less severe phenotype (CID‐G/AI) to those with AS and OS . Although patients with OS have a markedly restricted T‐cell repertoire, they do not share the same rearrangements.…”
Section: Genotype‐phenotype Correlation In Rag Deficiencymentioning
confidence: 91%
“…Analysis of the TCR and BCR repertoire identifies skewed usage of V(D)J segment genes and abnormalities of CDR3 length distribution. 23 We also see, as recently published 24 , that low IgA and IgM is associated with bronchiectasis in PID. Mutant RAG1 and RAG2 proteins with residual recombination activity in these patients likely provides antibody repertoire that may be sufficient during early childhood but immunodeficiency and progressive autoimmunity becomes apparent towards early adolescence.…”
Section: Discussionsupporting
confidence: 69%
“…We have previously shown that the severity of the clinical and immunological phenotype in patients with RAG mutations correlates with the residual recombination activity of the mutant recombinase-activating gene (RAG) protein (22), which may differently affect diversity and composition of T and B cell receptor repertoires (23), whereas NK cell differentiation proceeds unaffected. For patients with severe RAG mutations presenting with SCID, OS, or AS, HSCT represents the only option of definitive cure; however, an increased rate of allograft rejection has been observed as compared to patients with other forms of SCID (24, 25).…”
Section: Introductionmentioning
confidence: 99%